Improving Ionic Conductivity of Carboxymethyl Cellulose Solid Biopolymer Electrolyte with Assist from Dimethyl Carbonate - Mohd Ibnu Haikal Ahmad Sohaimy; Yusrina Yusof; Mohd Ikmar Nizam Mohamad Isa (Walailak University, 2024)
Indexed by Scopus